Leveraging neglected and underutilized plant, fungi, and animal species for more nutrition sensitive and sustainable food systems - Padulosi, S.; Cawthorn, D.M.; Meldrum, G.; Flore, Roberto; Halloran, A.; Mattei, F. (Elsevier, 2019)
As a result of the narrow focus of modern agriculture on a limited number of crops and animals, today the vast majority of edible plants, fungi, and animals is poorly addressed by research and development. This article highlights the rich diversity of neglected and underutilized species (NUS) and identifies opportunities and challenges for their use. Along with research and development attention, better marketing and consumer awareness on the benefits of neglected and underutilized species can play a critical role in sustainable promotion of NUS and enhance their role for resilience to climate change, food and nutrition security and income generation.